EXPLORING THE STUDENTS’ PERCEPTION OF TRANSLATION ACTIVITY IN POETRY CLASS - Gina Larasaty; Indra Yoga Prawiro (JELLT (Journal of English Language and Language Teaching), 2021)
Abstract Students’ perception of language learning has been an interesting topic for the researcher. The present study aims to investigate the students’ perception of translation activity in the Poetry classroom. The students’ perception was collected through questionnaire. The questionnaires contain 5 items that cover the students’ opinion about translation activity, students’ experience in Translation activity, students’ perception about the usefulness of translation activity, students’ preference about classroom interaction and students’ willingness of course length. Based on the result shows than Students has positive perception relate to Translation activity. They think that translation activity is important to be applied in the poetry classroom and can help them understand the poetry text. Students feel that translation activity is important, that is why they like it when they get assignments and working in group to translate. In Translating, they also prefer to use machine translation. Keywords: Perception, Translation Activity, Poetry Class